Critical incidents and post-traumatic stress symptoms among experienced registered nurses during the COVID-19 pandemic: A cross-sectional study - Sara Melander; Oili Dahl; Ann-Charlotte Falk; Veronica Lindström; Erik Andersson; Petter Gustavsson; Ann Rudman (Elsevier, 2024)
Background: Registered nurses working on the frontline during the COVID-19 pandemic encountered significant challenges, including exposure to critical incidents. Critical incidents refer to sudden unexpected clinical events that surpass an individual's ability to cope, leading to considerable psychological distress, which could potentially result in the development of post-traumatic stress disorder symptoms. Research has shown a high prevalence of post-traumatic stress disorder symptoms among healthcare workers, particularly those in close contact with COVID-19 patients. Objective: To assess the levels of post-traumatic stress symptoms among registered nurses in relation to exposure to working conditions during the COVID-19 pandemic, such as how much their work was affected by the pandemic, re-deployment, working hours hindering sufficient recovery between shifts and critical incidents. Design: Cross sectional study. Setting(s): The registered nurses working in multiple health care services covering all 21 geographic regions in Sweden. Participants: A total of 1,923 registered nurses, who are part of a Swedish national cohort and have been followed since their nursing education, were invited to participate in a survey in late September 2021 (15 to 19 years post graduation). Methods: The data were analyzed using descriptive statistics, unpaired t-tests, and one-way analysis of variance. Cohen's d was employed to quantify differences in mean levels between subgroups. Results: The response rate were 56.5 %. Over 50 % of experienced registered nurses reported significant disruptions to their work environments. In total, 85 % of registered nurses were exposed to at least one critical incident in their work during the pandemic, with 60 % facing organisational changes and nearly 50 % experiencing emotionally distressing situations. The exposure to work situations involving critical incidents consistently demonstrated strong associations with higher levels of post-traumatic stress disorder symptoms compared to those not exposed, with effect sizes ranging from moderate to high. Conclusions: This study underscores the profound impact that working conditions, such as redeployment and exposure to critical incidents, have on the mental health of registered nurses. We offer valuable insights into registered nurses' pandemic-related challenges, highlighting the need for support and interventions to prevent and manage critical incidents, ultimately promoting their well-being. We also highlight the significance of thorough workforce readiness planning for future pandemics and other challenging health care scenarios, such as staff shortage.